2017
DOI: 10.1007/s11356-017-9889-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional and bio-treated methods as dust suppressants

Abstract: Dust is an environmental, geotechnical, health, and economical hazard. Fugitive dust emanating along transportation systems such as roads, railways, and airports especially can have significant impacts on health, safety, material loss, cost of maintenance, and interfere with the facilities. Quantitative studies on the effectiveness of the proper dust palliatives and their environmental impact have been studied with a number of biological and chemical methods. The objective of this study was to establish a meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The results obtained from this work showed that microbially precipitated calcite was very much effective in controlling soil erosion, as proven by wind tunnel experiments. Naeimi and Chu [179] compared the effectiveness of dust control through the biotreatment method and conventional techniques. Sporosarcina pasteurii was used in their study to treat sand against dust emission.…”
Section: Applied On Bacteria Used Referencementioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained from this work showed that microbially precipitated calcite was very much effective in controlling soil erosion, as proven by wind tunnel experiments. Naeimi and Chu [179] compared the effectiveness of dust control through the biotreatment method and conventional techniques. Sporosarcina pasteurii was used in their study to treat sand against dust emission.…”
Section: Applied On Bacteria Used Referencementioning
confidence: 99%
“…Coal dust MICP (Urease microbes) [180] Coal dust MICP (Staphylococcus succinus) [181] Desert soil MICP (Indigenous bacteria) [182] Sand MICP (Sporosarcina pasteurii) [179] Sand (well-graded) MICP (Sporosarcina pasteurii) [56] F60 silica sand EICP (Urease enzyme) [183] Ottawa F-60 fine grained uniform silica sand Well graded silty fine sand Mine tailings EICP (Urease enzyme) [78] The erosion of deposits of mine tailings caused by wind erosion is one of the most serious environmental concerns [184,185]. Wind carrying mine tailings poses a threat to water bodies nearby and deteriorates air quality, which means serious risks to human and animal health [186].…”
Section: Specimen Tested Bio-stabilizer Referencementioning
confidence: 99%
“…MICP technology can effectively improve the erosion resistance of the surface of the embankment model to prevent and control damage caused by overtopping flow (Figure 16). Naeimi and Chu [123] performed wind tunnel tests to verify the ability of microorganisms to treat sand surfaces for dust suppression and wind erosion resistance and estimated the amount of biological dust suppressants needed, which was less than the amount of conventional dust suppressant currently used for road and airport field applications. To study the feasibility, stability, and vegetation recoverability of the field stabilization of surface sand, Gomez et al [109] conducted field tests of MICP-treated surfaces at a Canadian mine site.…”
Section: Erosionmentioning
confidence: 99%
“…However, these improvement and improvement methods have disadvantages such as high cost, long construction period and unfriendly to the environment during the construction process (Ali 2018). In recent years, With the development of environmental geotechnical technology (Bai et al, 2021a;Bai et al, 2017), Microbial Induced Calcite Precipitation (MICP) method, has been widely used in construction projects for foundation strengthening (Liu et al, 2019), dust and sand consolidation (Naeimi and Chu 2017) and concrete fracture repair (Lors et al, 2017;Justo-Reinoso et al, 2021). MICP technology, as a new soil improvement method, can form carbonate precipitation with excellent consolidation performance.…”
Section: Introductionmentioning
confidence: 99%